Children’s heart disease in sub-Saharan Africa: Challenging the burden of disease - Hewitson, John; Zilla, Peter P.T. (SA Heart Journal, 2017)
Children with heart disease in Africa have little or no access to treatment of any kind, and cardiac surgical services are virtually absent outside a handful of centres in a few of the wealthier nations. There is little reliable data concerning the prevalence of congenital or acquired heart disease in African children, but there is sufficient information to indicate that the burden of cardiac disease is vast. This major non-communicable disease is largely hidden, overshadowed by the incidence of communicable diseases. There is as yet little evidence of the hoped-for epidemiological transition toward non-communicable diseases amongst children in Africa. The burden of congenital heart disease is only part of the problem, with rheumatic heart disease (RHD) remaining the commonest cardiac problem, related to poor socioeconomic conditions. RHD is the most preventable form of cardiac disease, yet there is little preventive work being done. The many obstacles to developing paediatric cardiac care are discussed, and some possible ways forward are proposed.